Understanding Reserve Volatility in Emerging Markets: A Look at the Long-Run - Ricarda Demarmels; Andreas Fischer (Swiss National Bank, Study Center Gerzensee, 2003)
In this paper, we examine long-run determinants of cross-country variation in reserve volatility for 30 emerging market economies from 1973 to 2000. Reserve holdings and openness are found to be the most important explanatory variables of reserve volatility. The empirical results are robust for a range of control variables, including monetary variables, the degree of financial development, and the level of indebtedness. We view these results as establishing interesting stylized facts that may be helpful in evaluating reserve volatility as a crisis indicator.
Keywords: F31; F33; 330; Reserve Volatility; Emerging Markets; Openness; Bankenliquidität; Volatilität; Schwellenländer; Schwellenländer